Perancangan Dashboard Informasi Rumah Sakit dalam Mendukung Pengambilan Keputusan di RSUD Pameungpeuk Garut - Ismi Azizah; Tria Saras Pertiwi; Witri Zuama Qomarania; Hosizah Hosizah (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
The availability of timely, accurate, and relevant information is essential for supporting managerial decision-making in hospitals. However, information at RSUD Pameungpeuk Garut is primarily presented in conventional tabular reports, limiting its ability to meet the diverse information needs of different management levels. This study aimed to develop a hospital information dashboard prototype based on an assessment of users' information needs to support managerial decision-making. This study employed a qualitative approach within a Research and Development (R&D) framework using the Prototype model of the System Development Life Cycle (SDLC). Data were collected through observations, in-depth interviews, and Focus Group Discussions (FGDs) involving representatives from middle and lower management levels. The collected data were analyzed through data reduction, coding, categorization, and thematic analysis to identify users' information requirements, which subsequently informed the dashboard design.The findings revealed that information needs varied across management levels. Top managementrequired concise strategic information for organizational decision-making, middle management needed analytical information for monitoring and performance evaluation, whereas lower management required detailed operational information to support daily activities and routine reporting. Based on these findings, three dashboard prototypes were developed: strategic, tactical, and operational dashboards, each tailored to the specific information requirements of its intended users.The proposed dashboard prototype is expected to improve the accessibility and presentation of managerial information while supporting more effective, evidence-based decision-making. Furthermore, the findings provide a practical foundation for developing an integrated hospital information dashboard within the Hospital Management Information System (HMIS).